Influence of Caregiver and Peer Support in Adherence to Antiretroviral Therapy Amongst HIV Positive Adolescents Attending Murang’a County Hospital - Ndungu, Peter K.; Kimani, Makobu; Mose, John Mokua (International Journal For Research In Health Sciences And Nursing, 2020)
Introduction: The number of youth and adolescent infected with the Human Immunodeficiency Virus is increasing globally. In 2019 alone, an estimated 460,000 young persons between 10 to 24 years globally were reported to be newly infected with HIV. Antiretroviral therapy is an effective approach to management for adolescents living with HIV. Maximum suppression of the virus improves the quality of life and health outcome. In May 2020, Murang’a County reported viral load suppression in ages between 10-14 years of 87.2% while 15-19 years was 86.7%. However, viral suppression requires optimal drug adherence and behavior change that is influenced by approaches such as care givers and peer support. Optimum caregiver and peer support in sub-Saharan Africa is thought to hinder adolescent adherence to ART. The study aimed at assessing the influence of caregiver and peer support in adherence to antiretroviral therapy amongst HIV positive adolescents attending Murang’a county hospital. Methodology: A cross sectional study was carried out at Murang’a County Comprehensive Care Center among 93 purposively sampled adolescents and selected key informants. Data was collected using semi-structured questioners and key informant guides. Quantitative data was analyzed using SPSS; both descriptive and inferential statistical techniques were used. Qualitative data was manipulated manually through thematic analysis. Results: From the study, females (56%) and (44%) males took ART as prescribed. Many (65.7%) had secondary education whilst 19% had reached college/university level. Majority were Christians (92.4%) while Muslims were (5.7%). Mothers (37.6 %), fathers (9.7%), and both parents for (29%) took care of them. Respondents who did not attend support groups at Murang’a CCC cited distance (54%), being busy (15%) and bad timing (15%) as challenges. However, adolescents visiting Murang’a CCC received parent and school support. They ensured that their children took medication and visited clinic as required. Frequency of support group attendance was found to be statistically significant to adherence (p=0.002). Conclusion: Reinforcement of care giver support frameworks and promotion of peer support among ALWHIV is fundamental in fostering ART adherence among adolescents in Murang’a County. Availability of mHealth platforms such as WhatsApp is an opportunity to scaling up peer support among adolescents who experience challenges with distance and competing priorities.